Dendronized polydiacetylenes via photo-polymerization of supramolecular assemblies showing thermally tunable chirality. Issue 95 (15th November 2021) - Liu, Yanjun; Lin, Yaodong; Cao, Yuexin; Zhi, Aomiao; Chen, Jiabei; Li, Wen; Demir, Baris; Searles, Debra J.; Whittaker, Andrew K.; Zhang, Afang
Abstract : Dendronized polydiacetylenes showing thermoresponsiveness were fabricated via photopolymerization of assembled ribbons from amphiphilic dendronized diacetylene in aqueous solutions, which simultaneously showed thermally switchable chiralities. Abstract : Transformation of supramolecular chiral assemblies into covalent polymers integrates characteristics of supramolecular chemistry together with covalent entities, leading to fabrication of covalent chiral materials through versatile supramolecular chiral assemblies. Here, we report supramolecular assembly of an amphiphilic dendronized 10, 12-pentacosadiynoic amide (PCDA) in aqueous solutions to form twisted ribbons, which were transferred into covalent dendronized polydiacetylenes (PDAs) via photopolymerization. These supramolecular dendronized PCDA and the corresponding covalent dendronized PDAs showed unprecedent thermoresponsive properties. The thermally-induced dehydration and aggregations tuned reversibly their chiralities, which can be visually inspected through colour changes.